Substitusi Maggot (Hermetia Illucens) dengan Pelet terhadap Performa Ikan Maru (Channa marulioides) - Agus Setiawan; Sarmila Sarmila; Slamet Tarno; Hylda Khairah Putri (Faculty of Science and Technology University Ibrahimy, 2022)
The Market demand for maru still comes from natural catches. Collectors use maggots as a feed that supports the growth and life of maru fish. However, the chitin content and production costs of Maggot are obstacles in using Maggot as the main feed. This study aims to determine the combination of Maggot and artificial feed that provides the best growth rate and survival for maru. Seed maintenance lasts for 90 days. This study used a completely randomized design (CRD) with 4 treatments and 3 treatments, namely control (100% Maggot), Treatment A (Maggot 75% + Pellet 25%), Treatment B (Maggot 50% + Pellet 50%), Treatment C (Maggot 25% + Pellet 75%). The results showed that giving Maggot 50% + Pellet 50% was the best combination of feed to increase the growth and life of maru fish. The absolute length measurement of maru on 50% Maggot + 50% Pellet administration was 8.18 cm, and the absolute weight was 16.5 grams. The highest survival rate of maru fish reaches 70%.